Pembangunan Database Destinasi Pariwisata Indonesia Pengumpulan dan Pengolahan Data Tahap I - Yosafati Hulu (ComTech: Computer, Mathematics and Engineering Applications, 2014)
Considering the increasing need for local (government and community) in developing tourism destinations in the era of autonomy, considering the need to select the appropriate attraction according to the respective criteria, and considering the needs of businessmen travel / hotel to offer the appropriate attraction with the needs of potential tourists, it is necessary to develop a database of tourist destinations in Indonesia that is able to facilitate these needs. The database is built is a web-based database that is widely accessible and capable of storing complete information about Indonesian tourism destination as a whole, systematic and structured. Attractions in the database already classifiable based attributes: location (the name of the island, province, district), type/tourism products, how to achieve these attractions, the cost, and also a variety of informal information such as: the ins and outs of local attractions by local communities or tourists. This study is a continuation of previous studies or research phase two of three phases planned. Phase two will focus on the collection and processing of data as well as testing and refinement of the model design and database structure that has been created in Phase I. The study was conducted in stages: 1) Design Model and Structure Database,2) Making a Web-based program, 3) Installation and Hosting, 4) Data Collection, 5) Data Processing and Data entry, and 6) Evaluation and improvement/Completion.